Evaluating Consumer Acceptance of the Commercial Fleet of Methanol Vehicles in China - Li, Chengjiang; Negnevitsky, Michael; Wang, Xiaolin; Wang, Honglei; Hu, Yujie (Frontiers in Energy Research, 2021)
To enhance domestic energy security and reduce air pollution, China has accelerated the deployment of alternative fuel vehicles including methanol vehicles since the 2010s. Already completed pilot projects have demonstrated that methanol vehicles (commercial fleet) are economical, environmentally friendly, and technically mature. Therefore, the Chinese government aims to continually deploy methanol vehicles in coal-rich provinces. There are more than 20,000 methanol taxis in operation in China, it is important to evaluate the existing consumer acceptance of such commercial fleet before commercialization in a wider range. This paper proposes a conceptual model to identify consumer acceptance of methanol taxis. The model generates hypotheses that have been tested using surveys completed by taxi drivers of methanol vehicles in the cities of Xi’an (Shaanxi province) and Guiyang (Guizhou province). Results demonstrate that market, economic, and technological concerns strongly determine the consumer acceptance of the commercial fleet of methanol vehicles in China.